Perceptions of Vocational Interest: Self- and Other-Reports in Student–Parent Dyads - Holtrop, Djurre; Born, M.; de Vries, R. (2018)
The current study investigated how self- and other-ratings of vocational interests converge among student–parent dyads. Using the Personal Globe Inventory–Short, we obtained data from a pooled sample of 271 (high school senior and university) student–parent dyads. Participants rated their own vocational interests and those of the other dyad member. First, profile correlations revealed high levels of self-other agreement, moderate levels of assumed similarity, and low levels of similarity and reciprocity in vocational interests. These correlations are highly similar to those found in personality research. Second, profile elevation showed a reversed pattern compared to interest perceptions, with high levels of self-other agreement and moderate levels of assumed similarity, indicating that profile elevation may mostly be an artifact/rater bias and not a substantive factor. Ipsatization of the vocational interest scales somewhat reduced profile elevation bias. Third, same-gender dyads overestimated their similarity in vocational interests more than different-gender dyads.